Konstelasi Relasi Antar Aktor Dalam Gerakan Penolakan Tambang Emas Di Desa Pace Kecamatan Silo Kabupaten Jember 2016 - Yatim, Muhammad Nurul; Erawan, I Ketut Putra; Azhar, Muhammad Ali (Jurnal Nawala Politika, 2017)
ABSTRACT   This study aimed to analyze the movements and actors in the resistance movement of gold mining in the Pace village Subdistrict Silo, Jember regency. This research was using the Qualitative method include in-depth interviews and field in research studies,In addition collecting documents related to this research. This research had resulted, in finding the relationships between actors prone to be a trigger of conflict and led to the refusal movement made by the village community of Pace. Conflict of individuals who had an influence that made this conflict had became a mass conflict involving the community at large. Meantime, besides individual behalf, the state also had behalf for mining through PT Antam. The presence of the state in gold mining in the Pace village had become new chapter to the people who reject gold mining in the Pace village .   Keyword: Movement, Actor, Conflict.